2021
DOI: 10.1002/nop2.1142
|View full text |Cite
|
Sign up to set email alerts
|

The relationship between caregiver burden and self‐care agency of pregnant women with 0–6‐year‐old children

Abstract: Having a baby is one of the most important decisions in one's life.Pregnancy is the most important characteristic of a woman, and it has an important place in the life of the woman because it ensures the continuity of the generation (Güleşen & Yıldız, 2013). The global total fertility rate is 2.5 births per woman (United Nations,

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
0
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 21 publications
(24 reference statements)
0
0
0
2
Order By: Relevance
“…Previous research has shown that self-care ability is influenced by age, education level, marital status, family structure, physical condition, occupation, duration of hemodialysis, and payment method. [14] The research results showed no significant differences in general information such as age, marital status, gender, education level, and dialysis duration between the CK group and the ET group, as well as the comparison results of laboratory examination indicators such as parathyroid hormone, blood phosphorus, blood calcium, albumin, serum iron, blood potassium, blood calcium, blood urea, hemoglobin, and IWGR%, indicating that they are balanced and comparable. In addition, before intervention, there was a small difference in the 4 dimensions of self-care ability scores and total scores, indicating that the results of intervention treatment for the 2 groups of patients were reliable.…”
Section: Discussionmentioning
confidence: 92%
“…Previous research has shown that self-care ability is influenced by age, education level, marital status, family structure, physical condition, occupation, duration of hemodialysis, and payment method. [14] The research results showed no significant differences in general information such as age, marital status, gender, education level, and dialysis duration between the CK group and the ET group, as well as the comparison results of laboratory examination indicators such as parathyroid hormone, blood phosphorus, blood calcium, albumin, serum iron, blood potassium, blood calcium, blood urea, hemoglobin, and IWGR%, indicating that they are balanced and comparable. In addition, before intervention, there was a small difference in the 4 dimensions of self-care ability scores and total scores, indicating that the results of intervention treatment for the 2 groups of patients were reliable.…”
Section: Discussionmentioning
confidence: 92%
“…Araştırmacılar tarafından literatür eşliğinde oluşturulan11 soruluk form, sosyodemografik ve obstetrik özellikleri içerir (Ergun, 2022;Karataş Baran ve ark., 2020;Nguyen ve ark., 2022).…”
Section: Birey Tanıtım Formuunclassified
“…Gebelik sürecinin hem anne hem de yenidoğan lehine olumlu sonuçlanması için öncelikle annenin öz bakım gereksinimlerini yerine getirebilmesi, yeterli düzeyde öz bakım gücüne sahip olması ve bu konuda farkındalık geliştirmesi gerekir (Yılmaz & Beji, 2010). Literatürde gebelerin eğitim düzeyi, yaşı, sosyokültürel özellikleri, deneyimleri, gebelik sayısı, yaşayan çocuk sayısı, gebelik eğitimi alma ve gebeliği planlama, sosyal destek alma durumu, psikolojik iyilik hali, stres ve depresyon düzeyleri gibi faktörlerin öz bakım gücünü etkilediği belirtilmektedir (Ergun, 2022;Nguyen ve ark., 2022;Yılmaz & Beji, 2010).…”
Section: Introductionunclassified